2002
DOI: 10.1080/09583150120124487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timber Condition on Parasitization of Pine Weevil ( Hylobius abietis L.) Larvae by Entomopathogenic Nematodes under Laboratory Conditions

Abstract: The large pine weevil (Hylobius abietis L.) is one of the most important pests in coniferous reforestation in Europe. Larvae develop in the stumps of recently felled trees; the emerging adults feed on the bark of seedlings and may kill them. The ability of the entomopathogeni c nematodes Heterorhabditi s megidis and Steinernema carpocapsae to invade pine weevil larvae in Sitka spruce (Picea sitchensis) buried in moist sand was evaluated. Overall, four times as many H. megidis as S. carpocapsae invaded pine wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Unfortunately data were not collected on the size of either weevil larvae or parasitoid clutches. Armendariz et al (2002) reported that inoculation of timber with P. gigantea enhanced invasion of insects by S. carpocapsae, but reduced invasion by Heterorhabditis megidis Poinar, Jackson and Klein. In our trials, inoculation of stumps with T. koningii at felling did not facilitate either S. carpocapsae or H. downesi applied 24 months later, indeed, infection levels were somewhat reduced as noted above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately data were not collected on the size of either weevil larvae or parasitoid clutches. Armendariz et al (2002) reported that inoculation of timber with P. gigantea enhanced invasion of insects by S. carpocapsae, but reduced invasion by Heterorhabditis megidis Poinar, Jackson and Klein. In our trials, inoculation of stumps with T. koningii at felling did not facilitate either S. carpocapsae or H. downesi applied 24 months later, indeed, infection levels were somewhat reduced as noted above.…”
Section: Discussionmentioning
confidence: 99%
“…In our trials, inoculation of stumps with T. koningii at felling did not facilitate either S. carpocapsae or H. downesi applied 24 months later, indeed, infection levels were somewhat reduced as noted above. The facilitation of EPN reported by Armendariz et al (2002) may have been due to the degradation of P. gigantea-treated wood- Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, because Z. angusticollis nests can be partially buried in soil, the possibility exists that soil nematodes can migrate from the surrounding soil and penetrate wood in various stages of decomposition. Indeed, decayed wood appears to be very attractive to S. carpocapsae (Armendariz et al, 2002). Soft decomposed wood might provide a suitable substrate for the typical ambush/nictating behavior of S. carpocapsae and ultimately result in the successful invasion of wood-inhabiting hosts, as has been demonstrated in the pine weevil, Hylobius abietis (Armendariz et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, decayed wood appears to be very attractive to S. carpocapsae (Armendariz et al, 2002). Soft decomposed wood might provide a suitable substrate for the typical ambush/nictating behavior of S. carpocapsae and ultimately result in the successful invasion of wood-inhabiting hosts, as has been demonstrated in the pine weevil, Hylobius abietis (Armendariz et al, 2002). Therefore, the lack of foraging behavior outside the nest by Z. angusticollis does not necessarily preclude this termite species from encountering S. carpocapsae or other nematode species in their natural environment.…”
Section: Discussionmentioning
confidence: 99%